Artificial amplification of warming trends across the mountains of the western United States. Issue 1 (13th January 2015) - Oyler, Jared W.; Dobrowski, Solomon Z.; Ballantyne, Ashley P.; Klene, Anna E.; Running, Steven W.
Abstract Observations from the main mountain climate station network in the western United States (U.S.) suggest that higher elevations are warming faster than lower elevations. This has led to the assumption that elevation‐dependent warming is prevalent throughout the region with impacts to water resources and ecosystem services. Here we critically evaluate this network's temperature observations and show that extreme warming observed at higher elevations is the result of systematic artifacts and not climatic conditions. With artifacts removed, the network's 1991–2012 minimum temperature trend decreases from +1.16°C decade−1 to +0.106°C decade−1 and is statistically indistinguishable from lower elevation trends. Moreover, longer‐term widely used gridded climate products propagate the spurious temperature trend, thereby amplifying 1981–2012 western U.S. elevation‐dependent warming by +217 to +562%. In the context of a warming climate, this artificial amplification of mountain climate trends has likely compromised our ability to accurately attribute climate change impacts across the mountainous western U.S.